The girl from Paris - Aiken, Joan, 1924- (G.K. Hall, 1983)
The Paget Family Saga comes to a riveting conclusion in this historical romance reissue from legendary author Joan Aiken Love and scandal are close on her heels... Ellen Paget moves to Paris, longing to flout convention and spread her wings in Society. She wants nothing to do with the charming Hon. Benedict Masham, an old family friend who's made it his business to look after her welfare. But when tragedy and scandal force Ellen back to England, it takes all her ingenuity to keep her family safe, and Benedict's steadfast help and unwavering support are suddenly indispensable... What readers love about The Paget Family saga: "Romance and high adventure." "Cracking entertainment." "Vivid vocabulary and vibrant imagery." "A relatable, believable heroine." "Period romance full of thrills and chills."